A Review of Literature in Applied Five Factor Model of Personality among Staff at Workplace - Mehrad, Aida (Open Science Journal, 2020)
Staff feeling and performance at the workplace and obtaining a high level of outcomes drive from various factors; in truth, the human being is complicated and there are numerous internal and external factors that have an impact on it. Personality determined as one of these main internal factors that introduced individuals at their personal and social life; furthermore, recognizing its deep definition and effect on the approach and accomplishment of staff stays valuable and essential. Personality consists of five main factors: neuroticism, extraversion, openness, agreeableness, and conscientiousness that each person based on these factors illustrates dissimilar behavior and response. Additionally, the person introduced or well-known via these factors. Incidentally, the present literature review surveys five personality factors amongst staff in the context of the five-factor model and analyzes staff performance and behavior at the workplace. Overall, the study emphasized the role of managers, leaders, supervisors, etc. at the workplace to identify and evaluate staff personality, because by recognizing staff personality managers can offer a suitable solution to coping and solving any type of conflict or issue.